Finding the ‘sweet spot’ between customisation and workflows when optimising ePrescribing systems: a multisite qualitative study - Aziz Sheikh; Stephen Malden; Catherine Heeney (BMJ Open)
Objectives The introduction of ePrescribing systems offers the potential to improve the safety, quality and efficiency of prescribing, medication management decisions and patient care. However, an ePrescribing system will require some customisation and configuration to capture a range of workflows in particular hospital settings. This can be part of an optimisation strategy, which aims at avoiding workarounds that lessen anticipated safety and efficiency benefits. This paper aims to identify ePrescribing optimisation strategies that can be translated into hospitals in different national settings. We will explore the views of professionals on the impact of configuration and customisation on workflow.Design This paper draws on 54 qualitative interviews with clinicians, pharmacists and informatics professionals with experience of optimising ePrescribing systems in eight hospital sites and one health system, in four different countries. Interview transcripts were analysed using an inductive thematic analysis.Setting Secondary and tertiary care hospitals in the UK, USA and mainland Europe.Participants Fifty-four healthcare workers with expertise in clinical informatics.Results Five identified themes following thematic analysis showed that optimisation of ePrescribing systems can involve configuration and/or customisation. This can be a strategy to combat workarounds and to respond to local policy, safety protocols and workflows for particular patient populations. However, it can result in sites taking on responsibility for training and missing out on vendor updates. Working closely with vendors and other users can mitigate the need for extensive system modification and produce better outcomes.Conclusions Modifying an ePrescribing system remains key to enhancing patient safety, and better captured workflow remains key to optimisation. However, we found evidence of an increasingly cautious approach to both customisation and configuration among system users. This has led to users seeking to make less changes to the system.